Policing sex in the Sunflower State the story of the Kansas State Industrial Farm for Women - Perry, Nicole (University Press of Kansas, 2021)
"Policing Sex in the Sunflower State recounts the little-known story of Chapter 205, a state law that gave the Kansas Board of Health broad powers to quarantine individuals with venereal diseases. Though the law was officially gender-neutral and the state initially detained a few men under the ordinance, Chapter 205 was almost exclusively enforced against women by the early 1920s. State officials quarantined women alongside regular female prisoners at the Kansas State Industrial Farm for Women (KSIFW) throughout the 1920s and 1930s, with women sentenced under Chapter 205 averaging 71% of the total inmate population between 1918 and 1942. Their confinement at the WIF was indefinite, with doctors and superintendents deciding when they were physically and morally "cured" enough to reenter society; in practice, women detained under Chapter 205 spent an average of four months at the Farm. Though the numbers of women imprisoned under Chapter 205 declined in the 1940s, women were quarantined under the law as late as 1955. Policing Sex in the Sunflower State tells the story of Chapter 205 through the experiences of three groups of women-the activist women who lobbied to create the Farm, the professional women who ran it, and the working-class women who were imprisoned there-in order to explore the intersections of social hierarchies in interwar Kansas"--